Regional differences in the incidence of Alzheimer’s disease and related dementias in South Carolina - Amoatika, Daniel A.; Miller, Maggi C.; Adams, Robert J.; Milano, Nicholas J. (Frontiers in Neurology, 2025)
IntroductionThere is an increase in the population of older adults, 65 years or older in South Carolina. Socio economic and environmental factors are linked to the diagnosis of Alzheimer’s Disease and related dementias (ADRD). The aim of this study was therefore, to characterize the incidence of ADRD by public health regions (PHR).MethodsWe estimated the incidence of ADRD for 2021using data from South Carolina Alzheimer’s Disease Registry (SCADR) and the Annual County Resident Population Estimates (ACRPE). The incidence of new cases per 100, 0000 population for each county, and PHR, and age-adjusted ADRD specific diagnosis were estimated. Poisson regression modeling was used to compare crude and ADRD specific incidence by PHRs. The incidence of ADRD by counties and PHRs was visualized using TIGERline files.ResultsA total of 18,955 registrants from the SCADR were included in this study. About 38% of the participants were between 75 and 84 years. Additionally, about 79% of the registrants had Alzheimer’s (AD) diagnosis. The crude incidence of ADRD was higher in the Pee Dee PHR (896 per 100,000). Among ADRD specific diagnosis, AD incidence was higher in the Pee Dee PHR (727 per 100,000), Vascular dementia (VaD) and Mixed dementia incidences were higher in the Upstate PHR. The crude incidence of ADRD differed significantly across all the PHRs (p < 0.05).DiscussionRegional differences in the incidence of ADRD suggest possible disparities in healthcare access, socioeconomic conditions and geographical factors. Targeted interventions, and early screening among young populations should be prioritized.